2007
DOI: 10.1128/aem.00848-07
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cryptosporidium Genotype in Wild Australian Mice ( Mus domesticus )

Abstract: A total of 250 mouse fecal specimens collected from crop farms in Queensland, Australia, were screened for the presence of Cryptosporidium spp. using PCR. Of these, 19 positives were detected and characterized at a number of loci, including the 18S rRNA gene, the acetyl coenzyme A gene, and the actin gene. Sequence and phylogenetic analyses identified two genotypes: mouse genotype I and a novel genotype (mouse genotype II), which is likely to be a valid species. Cryptosporidium parvum, which is zoonotic, was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…Relative to Cryptosporidium, the prevalence was higher than found for murids by other authors, where values were around 10% (Torres et al 2000, Foo et al 2007.…”
Section: Discussioncontrasting
confidence: 43%
“…Relative to Cryptosporidium, the prevalence was higher than found for murids by other authors, where values were around 10% (Torres et al 2000, Foo et al 2007.…”
Section: Discussioncontrasting
confidence: 43%
“…In this study, the overall Cryptosporidium prevalence in 723 rodents in China was 11.5%, which was within the reported range of 5.0% to 39.2% (11)(12)(13). The infection rate (21.8%) in pet rodents was apparently higher than infection rates in wild (6.8%) and laboratory rodents (1.9%).…”
Section: Discussionmentioning
confidence: 74%
“…Kimura et al (2007) found C. parvum, C. meleagridis, and unknown Cryptosporidium genotype in brown rats. In Australia, 19 of 250 wild Australian mice (Mus domesticus) were Cryptosporidium positive and Mouse genotype I and II were detected (Foo et al, 2007). In China, four new Cryptosporidium genotypes were identified, including the hamster genotype, chipmunk genotype III, and rat genotypes II and III from 18 rodent species (Lv et al, 2009).…”
Section: Discussionmentioning
confidence: 97%